Laser Enrichment Device Stimulates Broiler Laser-Following Behavior While Increasing Individual Bird Locomotion and Pen-Wide Movement - Meyer, Meaghan M.; Johnson, Anna K.; Bobeck, Elizabeth A. (Frontiers in Animal Science, 2021)
Genetic selection for fast growth rate and high breast muscle yield in modern broilers has unintended effects on animal welfare and behavior, namely in terms of inactivity and leg disorders. We hypothesized that exercise stimulated through environmental enrichment could positively stimulate pen-wide activity and improve bird welfare. The study objectives were to implement a laser enrichment device to motivate active and feeding behaviors throughout the pen. Twelve hundred Ross 708 broilers were randomly assigned to enrichment (LASER; laser enrichment, or CON; no laser enrichment) for 49 d. Seventy focal birds were randomly assigned to 14 video-recorded pens for behavioral analysis, including focal bird home pen behavior and walking distance. Pen-wide activity was also measured during the 4-min laser periods, four times daily, d0–8, and 1 day weekly, wk 1–6. Focal birds were gait scored wk 1–6, and were euthanized on d42 for tibia bone mineral content, density, and bone breaking strength analysis. Time spent active was increased in LASER-enriched birds compared to CON on wk 3–5 by up to 214% (wk 4), and percent of time at the feeder was increased in LASER-enriched birds by 761% on wk 4 (P < 0.05). Peak percent of birds following the laser (LASER-enriched pens only) was observed on d0 (8.52%). Over wk 1–6, peak laser-following behavior was observed on wk 3 (3.07% of birds). Percent of birds moving during laser periods was increased in LASER-enriched pens on d0, 1, 2, 6, 7, and 8, with a percent increase of 68.7% observed on d1 (P < 0.05). Percent of birds moving (laser-following or not) was increased on wk 1, 3, and 4 in LASER-enriched pens, with an increase of 69.7% observed on wk 4 (P < 0.05). No differences were found in tibia measures. These data indicate that laser enrichment stimulated voluntary locomotion through wk 5 and laser-following behavior through wk 6, and that the relatively small percent of birds actively following the laser stimulated pen-wide movement above the level of the CON through wk 4 on study.